1987
DOI: 10.1016/0035-9203(87)90055-1
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of acute diarrhoea in a rural community in Imo State, Nigeria

Abstract: As part of an evaluation of a water supply and sanitation project, a baseline cross-sectional study of diarrhoea, and its putative risk factors, was conducted in 5 villages in Imo State, Nigeria. Data were collected from 4641 and 5920 persons during surveys in the dry and wet seasons, respectively. 8 d period prevalence rates for diarrhoea ranged from 5 to 50%, with the highest rates occurring in the 6 to 23 month age group. Diarrhoea was associated with up to 75% of all illnesses in young children and with ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0
3

Year Published

1988
1988
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 3 publications
3
19
0
3
Order By: Relevance
“…The primary caregivers in the households in the BHDSS have very low educational background and significant gaps in knowledge and perception of diarrheal illness and its management, which has been seen elsewhere 13. The study found a higher prevalence of diarrhea in children < 2 years of age, particularly among the 12–23 months age group compared with the 0–11 and 24–59 months age groups, similar to the findings in other African settings 1416…”
Section: Discussionsupporting
confidence: 88%
“…The primary caregivers in the households in the BHDSS have very low educational background and significant gaps in knowledge and perception of diarrheal illness and its management, which has been seen elsewhere 13. The study found a higher prevalence of diarrhea in children < 2 years of age, particularly among the 12–23 months age group compared with the 0–11 and 24–59 months age groups, similar to the findings in other African settings 1416…”
Section: Discussionsupporting
confidence: 88%
“…aggregation) of diarrhoeal disease over time in certain individuals, indicating that some people are more susceptible to diarrhoea than others. This confirms and extends observations made before the HIV pandemic [10-12]. Interestingly, this aggregation of disease is still seen in severely immunosuppressed adults with CD4 counts of less than 200 cells/μL, so it seems unlikely to be attributable to variations in cell-mediated immunity.…”
Section: Discussionsupporting
confidence: 88%
“…It is well known that intestinal helminth infections display aggregation [6-8] meaning that certain susceptible individuals carry large numbers of worms and therefore a disproportionate fraction of the burden of disease [9]. There is also some evidence that incidence of diarrhoeal disease is aggregated in some highly susceptible children [10,11] and adults [12] in an analogous way. In this paper we analyse diarrhoea and infection separately which allows us to demonstrate that the disease-to-infection ratio is elevated at all stages of HIV infection.…”
Section: Introductionmentioning
confidence: 99%
“…We did not find the same result in the Iraq study 18 in which we found no association between wealth and diarrhoea. Further, Osumane 19 , Huttly et al 20 and El Samani et al 21 did not find a significant association between diarrhoea and wealth. Contrary to the above findings, Boadi and Kuitunen 22 reported that children from poor homes had higher diarrheal incidence than their medium wealth and high wealth counterparts.…”
mentioning
confidence: 87%